A christian dimension to poverty discourse in Nigeria (2011)
Poverty, which manifests in various forms, has been a major problem for mankind and a source of concern for successive administrations at various levels in Nigeria. Given this, several attempts have been made towards its reduction, eradication and alleviation, but no major success has been recorded, thus majority of the populace continues to wallow in abject poverty while ironically some have more than enough. Several scholars have worked on different perspectives of poverty. In this piece, an attempt is made to discuss the subject matter from a Christian religious view point so as to understand religion as a major factor in the issue of poverty in Nigeria. In other words, the Church is to be understood as an agent of poverty alleviation and possible harbinger of poverty. A pragmatic religious approach to poverty alleviation is provided as recommendations.